An Analysis of Investment Incentive Policies in Canada - Harman, Francis J. (My University, 1977)
Investment incentive policies have been major policy instruments used in Canada and elsewhere to achieve economic growth and stabilization. In this study an attempt is made to isolate the specific effects contained in these policies, and to measure their impact on investment expenditures in Canada. There are three major sections to the study. First, various well-known models of investment behaviour are used to illustrate how investment incentive policies may be expected to influence investment expenditures. Secondly, a group of major Canadian incentive policies are described in detail, together with an outline of the institutional framework in which the policies were conceived and operated. Thirdly, these major policies are incorporated into investment functions to test for their impact on investment expenditures. From the empirical analysis, the investment incentive policies do not appear to have influenced investment expenditures to any substantial degree. At the same time the cost of these policies in terms of revenue foregone has been substantial. The major conclusion is that the case for investment incentive policies as instruments of short run stabilization policy is extremely weak.
Keywords: investment, incentive, policies, economic growth, stabilization, Canada, influence, expenditures, institutional framework